1972
DOI: 10.1172/jci106945
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the identity of the major apoprotein in low density and very low density lipoproteins in normal subjects and patients with familial hyperlipoproteinemia

Abstract: A B S T R A C T The major apoprotein (s) from human plasma low density lipoproteins was isolated and compared with a major protein fraction (fraction I) from very low density lipoproteins (VLDL). Fraction I had been previously found to comprise approximately 40% of the total protein of VLDL. Fraction I from VLDL and apoLDL from normal subjects were indistinguishable in amino acid compositions and circular dichroic spectra. They yielded indistinguishable displacement curves of LDL-'I by radioimmunoassay and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1973
1973
1977
1977

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Our study confirmed the report of Gotto et al [24], that ApoB in type IIa hyperlipoproteinemia is immunochemically identical to ApoB from normal plasma. In addition, all the identified apolipoproteins and their polypeptides in type Ila hyperlipoproteinemia are immunochemically and electrophoretically identical to those from normal plasma.…”
Section: Resultssupporting
confidence: 93%
“…Our study confirmed the report of Gotto et al [24], that ApoB in type IIa hyperlipoproteinemia is immunochemically identical to ApoB from normal plasma. In addition, all the identified apolipoproteins and their polypeptides in type Ila hyperlipoproteinemia are immunochemically and electrophoretically identical to those from normal plasma.…”
Section: Resultssupporting
confidence: 93%
“…Lipid-free LDL and VLDL were prepared by delipidation at 4 C C with diethyl ether-ethanol (3:1). 20 The apoB was purified by fractionation of lipid-free LDL on Sephadex G-150 as described previously. 20 Antisera against apoB were raised in goats and were partially purified by affinity chromatography using LDL-Sepharose.…”
Section: Preparation Of Lipoproteens Apob and Antiseramentioning
confidence: 99%
“…20 The apoB was purified by fractionation of lipid-free LDL on Sephadex G-150 as described previously. 20 Antisera against apoB were raised in goats and were partially purified by affinity chromatography using LDL-Sepharose. 17 The antisera gave precipitin lines of complete identity against LDL and VLDL but did not react with human serum albumin, high density lipoproteins (HDL) and its major apoproteins, apoA-I or apoA-II, or the apoC proteins, 21 either on double gel diffusion plates or in the electroimmunodiffusion (EID) system described below.…”
Section: Preparation Of Lipoproteens Apob and Antiseramentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these apoproteins have been isolated and characterized from human plasma and most of them are present in more than one lipoprotein family. Apoprotein B constitutes more than 95% of the protein moiety of low density lipoproteins (LDL) (8), and also represents 22 and 30-40% of the protein moieties of chylomicrons and VLDL, respectively (9,10). The apoprotein B appears to be required for the transport of lipoprotein particles out of the absorptive cell and into the lymph.…”
Section: Introductionmentioning
confidence: 99%